Towards a more integrative paradigm in fisheries assessment: genetic reference points - Seijas-Díaz, Iria; Presa, Pablo (Frontiers in Marine Science, 2025)
Fishery management decisions based solely on demographic models risk unintended and detrimental socio-economic consequences. Integrating biologically relevant metrics into stock assessments is crucial for sustainability amidst anthropogenic and environmental stressors (e.g., invasions, overfishing, pollution, global ocean change). In this work the authors aim to develop Genetic Reference Points (GRPs) for monitoring and evaluating the genetic status of fisheries which are patently absent from the official assessment. Complementary to demographic metrics, incorporating genetic analogs such as the Basal Genetic Reference Point (BGRP), the Target Genetic Reference Point (TGRP), the Limit Genetic Reference Point (LGRP), the trigger Genetic Reference Point (tGRP), and Genetic Structural Reference Point (GSRP) is now a viable approach. Using long-term genetic data series of the European hake, Merluccius merluccius, we show that current GRPs can significantly contribute to quantify a critical biological dimension across spatial (metapopulation structure) and temporal (evolution of genetic background under exploitation) scales. Therefore, we propose the systematic monitoring of spatiotemporal genetic diversity in other fisheries using established metrics such as the effective size (Ne​) and novel metrics, e.g., Z_LDNe​, D_LDNe and a Genetic Resilience Index (GRI) which relates the amount of change in Ne between fishery moments. We advocate for an interdisciplinary effort to integrate GRPs into algorithms and analytical models to enhance their predictive capacity in assessing the comprehensive biological status of exploited fisheries. Establishing robust GRPs at defined historical baselines, following a systematic roadmap, would provide future generations with scientifically sound criteria to assess genetic over fishing and to implement rebuilding strategies where appropriate.